The Air War against North Vietnam: the Thanh Hoa Railroad and Highway Bridge (Part Four) - van Geffen, Theo (Air power history, 2019)
According to TAWC, this laser system had the potential of improving weapons delivery accuracies by as much as 50 percent. The operation concept included the demonstration of the feasibility of laser semi-active guidance for conventional munitions, the determination if any improvements in the M-117 Circular Error Probability (CEP) could be attained with laser guidance, and the acquisition of information relative to operational capabilities and limitations of a laser guided bomb modification. Two contracts were let, one to Texas Instruments (TI, effective November 16, 1965), and one to North American Aviation's Autonetics (effective June 3, 1966), respectively Project 1559Y1 and 1559Y2, to fabricate guidance and control kits to attach to the M-117 bomb to give it the capability to home on the radiation from a target marked with a ground-based or airborne laser illuminator. According to TAWC such use of the bomb would work better in South Vietnam, but there would be a problem without the FAC to illuminate the target.